The association of ToRCH infection and congenital malformations: A prospective study in China. (September 2019) - Wang, Yuanyuan; Li, Shaoping; Ma, Nana; Zhang, Quanhua; Wang, Haiyan; Cui, Jingjing; Wang, Shijin
Abstract: Objective: ToRCH infections (toxoplasmosis, rubella, cytomegalovirus and Herpes simplex virus) have long been known to be associated with bad obstetric outcomes. Little information is available about the impact of ToRCH infection on reproduction in china nearly for ten years. We designed a prospective study among 1863 pregnant women to investigate the association of ToRCH infection and congenital malformations. Study design: All participants had set up a maternal health Handbook and were managed through the maternal and child health care system. They underwent regular pregnancy check-up, including physical measurements (weight, abdominal circumference and blood pressure), laboratory examinations (blood, urine) and ultrasound scan. ToRCH IgM antibodies were tested by chemiluminescence immunoassay. Results: 102 participants were infected with ToRCH and the total infection rate was 6.06% (102/1683). CMV infection rate (3.15%, 53/1683) was the highest. The positive rate of ToRCH IgM antibodies increased significantly in participant with upper respiratory tract infection (14.6%, 32/219) or with adverse pregnancy history (4.8%, 70/1464). Among 85 ToRCH infected participants, adverse pregnancy outcome were observed in 57 cases which included abortions (31.8%, 27/85), premature births (8.2%, 7/85), congenital malformations (12.9%, 11/85), and stillbirths (9.4%, 8/85). Furthermore, congenital malformations was much higher than that in those without ToRCH infection (1.1%, 17/1598) (P＜0.001). Conclusion: ToRCH infection was a significant risk factor of severe damage to the fetus, especially congenital malformations. ToRCH screening for pregnant women can reduce the incidence of adverse pregnancy and prevent birth defects in china.